2021
DOI: 10.1097/jom.0000000000002180
|View full text |Cite
|
Sign up to set email alerts
|

Absenteeism-Related Wage Loss Associated With Multimorbidity Among Employed Adults in the United States

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…While studying an entire region, Stearns and White, observed decreased absence among categories of workers entitled to receive PSL via a state mandate; this investigation also found an 18% decrease in overall absence among all workers in the state, even those not directly covered by the law, suggesting the benefits of PSL may extend beyond the covered workers 31 . Two other studies did not find a significant association between PSL and worker absence 27,34 …”
Section: Resultsmentioning
confidence: 61%
See 4 more Smart Citations
“…While studying an entire region, Stearns and White, observed decreased absence among categories of workers entitled to receive PSL via a state mandate; this investigation also found an 18% decrease in overall absence among all workers in the state, even those not directly covered by the law, suggesting the benefits of PSL may extend beyond the covered workers 31 . Two other studies did not find a significant association between PSL and worker absence 27,34 …”
Section: Resultsmentioning
confidence: 61%
“…Findings on absence from work were mixed, with four reporting mixed results within the same study 22,31,36,49 . Ten studies investigating absence from work found that PSL increased worker absence, 22,23,29,31–33,36,37,49,53 one reported fewer overall absences in the workplace, 12 and seven did not establish a significant relationship between PSL and worker absence 22,27,31,34,36,45,49 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations